If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7c + 3 + -5c = 15 Reorder the terms: 3 + 7c + -5c = 15 Combine like terms: 7c + -5c = 2c 3 + 2c = 15 Solving 3 + 2c = 15 Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + 2c = 15 + -3 Combine like terms: 3 + -3 = 0 0 + 2c = 15 + -3 2c = 15 + -3 Combine like terms: 15 + -3 = 12 2c = 12 Divide each side by '2'. c = 6 Simplifying c = 6
| 3x+8=5x+9 | | -4f+1=13 | | 3x+7=2x+4 | | 125x=25x+1 | | 5m-12-3m=2m+8 | | -9d-1=17 | | 26x+2=18x+48x+6 | | 2(x+4)+36=-3x | | -2x-4=8 | | 5X+12=8X-12 | | 2a+5b=10a+14b | | -12x+3=51 | | -4x-20+9x=-5 | | 5*(x+3)=3*(2x-1) | | 3G-49=-7 | | 11x-13-27-13x=0 | | -12x-3=-51 | | 11xcv+456-35yU=o | | 7+4x=10x-11 | | 15a-54=-9 | | 5x+7=2x+4 | | -56=20-(-e) | | 11x-24=-2 | | x-(-74)=-22 | | 8-2y=2y-2-y | | 4.7=-8.3q | | 4d-35=-3 | | 9+4y=3(4-y) | | 2.7y=-18 | | 18=-5y-7 | | 4(w-3)=8w | | 3k-7=14 |